2014
DOI: 10.2217/nnm.14.209
|View full text |Cite
|
Sign up to set email alerts
|

Nanocapsules Loaded with Iron-Saturated Bovine Lactoferrin have Antimicrobial Therapeutic Potential and Maintain Calcium, Zinc and Iron Metabolism

Abstract: The study concludes that bLf and nanoformulated Fe-bLf are more effective in the treatment of Salmonella-infected mice than ciprofloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…The latter was evidenced by up- and down-modulation of cytokines involved in innate and adaptive immune responses as well on hematopoietic cytokines, with a key role in the generation of both granulocyte (PMN neutrophils) or agranulocyte (monocytes/macrophages) phagocytes [6]. Thus, iron-loaded bLf nanocapsules seem to evoke the convergence of innate and adaptive immune responses of pro- and anti-inflammatory cytokines resulting in the protection toward typhoid infection and concomitant intestinal inflammation.…”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter was evidenced by up- and down-modulation of cytokines involved in innate and adaptive immune responses as well on hematopoietic cytokines, with a key role in the generation of both granulocyte (PMN neutrophils) or agranulocyte (monocytes/macrophages) phagocytes [6]. Thus, iron-loaded bLf nanocapsules seem to evoke the convergence of innate and adaptive immune responses of pro- and anti-inflammatory cytokines resulting in the protection toward typhoid infection and concomitant intestinal inflammation.…”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%
“…The biotechnological development of formulations of Lf as nanoparticles for potential clinical use, in addition to Lf-hydrolysate, and native Lf alone or in combination with probiotics, may have application for the control of infections and inflammation [6,74,130,184,190,191]. …”
Section: Lactoferrin As Anti-inflammatory In Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different microRNAs (miRNAs) responsible for iron regulation in different organs were identified and it was found that the NCs inhibited survivin and its different isoforms to induce apoptosis via both extrinsic as well as intrinsic pathways [10]. We have delivered drug (Taxol) and FebLf to treat colon [9,10] and breast xenograft cancers [11] and Salmonella typhimurium infected mice [12] using these NCs, without inducing any cytotoxicity. More recently, we validated the efficacy and safety of these nanocapsules to deliver anti-inflammatory Fe-bLf [13], and Indian herbal bioactive from Lakshadi Guggul glycoprotein (LG-GP) [14] to inflamed joints in collagen-induced DBA/1 arthritis (CIA) model.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We have elaborately validated and deciphered the internalization and the anti-cancer activity of these NCs in both in vitro and in vivo models of breast/colon cancers [19,21], microbial infections [12] and osteoarthritis [13]. We also compared the number of RBCs in the treatment groups and in control mice and found that nanolactoferrin treated mice were healthy with improved blood cell counts [9,10,11].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%